Wykorzystanie barw w kształtowaniu wizerunku instytucji kultury - Baczyńska-Hryhorowicz, Alicja (Załącznik Kulturoznawczy, 2021)
Colors are the basic element of the visual identity system, which is important in shaping the image of an organization among target groups. Deliberate use of colors can help consolidate its positive image among the recipients, which will translate into achieving its strategic goals. The article attempts to answer the question of how institutions can use colors to shape their image. In the first part of the work, the issue of image is discussed. The second section presents the general characteristics of colors, their psychophysical and symbolic properties, and then the possibilities to use colors in the visual identification system (logotype, promotional prints, website, building space). In the third part, theoretical principles are confronted with practice. The ways of using colors in shaping the image of three cultural institutions in Kraków (Opera, Philharmonic, MOCAK Museum of Contemporary Art in Krakow) are described, based on ethnographic research (participant observation, interviews with employees). Data analysis allowed to distinguish ways of using colors and functions they perform (practical and symbolic).